PENERAPAN PERMAINAN KOCOK ARISAN DALAM MENGEMBANGKAN KETERAMPILAN MEMBACA PERMULAAN PADA ANAK USIA 5-6 TAHUN - Halida, Halida (Jurnal Visi Ilmu Pendidikan, 2020)
AbstrackThe purpose of this study is to develop the preliminary reading skills by using the arisan shake game. The method used is descriptive method.The techniques used are observation and interview techniques. Data Analysis Techniques used in this research are data collection, data reduction, conclusion, drawing/verification. Data analysis used in this study is Percentage Descriptive Analysis. Subjects in this study were kindergarten children aged 5-6 years, located in Primanda Untan Kindergarten, Jalan M. Sjafei Pontianak.In children's lives, playing has important meaning. Every healthy child always has the urge to play.Fun learning for early childhood is playing. Early childhood reading starts from reading pictures to letters.Early childhood reading starts from reading pictures to letters. In this study researchers gave a game of social gathering so that the children were interested and motivated to do the learning activities provided by the teacher, especially reading the beginning.The results of this study from the aspect of interest of children aged 5-6 years in Primanda Untan kindergarten have a "high" interest in reading the beginning.This means that the child has a high heart tendency towards the game of social gathering which is presented by itself due to the needs of the child himself. Furthermore, the child is very interested or motivated to pay attention and then do a preliminary reading activity which is done with a charcoal shake game first.In the game, the observations show that the child is very attentive and enjoys an activity with a sense of pleasure. Judging from the aspect of motivation the percentage is "High enough", meaning that children aged 5-6 years in Primanda Untan Kindergarten are attentive and enthusiastic in the activity, the children have a hard working attitude in carrying out the game to completion.The response of children when given learning in developing interest and motivation with the arisan shake game is good. Good means that children respond well to the game by wanting to do games without coercion. They approached and held the toy out of curiosity, and most importantly the children were very cooperative to carry out the game from start to finish.